2014
DOI: 10.4028/www.scientific.net/amm.633-634.413
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior, Mechanical Property and Microstructure of Low-Density Polyethylene Filled by Diatomite

Abstract: Diatomite was treated by titanate coupling agent and blended with low-density polyethylene (LDPE) by the method of melt-mixing blend. The performance of the blends, such as thermal behavior, mechanical property and microstructure, were analyzed with differential scanning calorimetry, thermo-gravimetric analysis, tensile strength testing and scanning electron microscopy. The results showed that influenced the crystalline behavior of LDPE phase in the blends and made the crystallization rate of LDPE phase decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
0
0
Order By: Relevance
“…Both factors, namely the amount of reinforcing filler and the chemical modification, showed a synergistic effect. This synergistic effect was also described by the study of the research reported in [26][27][28].…”
Section: Mechanical Propertiessupporting
confidence: 67%
“…Both factors, namely the amount of reinforcing filler and the chemical modification, showed a synergistic effect. This synergistic effect was also described by the study of the research reported in [26][27][28].…”
Section: Mechanical Propertiessupporting
confidence: 67%